Consumer’s Purchase Intention Towards Sustainable Fashion Products: Effect of Perceived Consumer Effectiveness and Attitude - Annisa Tusholihah; Liza Nora (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: The existence of fast fashion as an environmentally unethical business model has an impact on increasing excessive consumption of fashion products. Sustainable fashion was created as a response to preventing and reducing negative impacts on this phenomenon. The idea of sustainable fashion is a love for the environment that shows up in our clothing choices and sustainable living habits.Purpose: This research aims to determine the influence of perceived consumer effectiveness on consumer intentions to buy sustainable fashion products with attitude as a mediating variable.Design/methodology/approach: conducted using a quantitative design. The total sample was 196 respondents using the purposive sampling technique. Quantitative data was collected through an online questionnaire via Google Form and distributed to people who met the sample size requirements: consumers over 17 years old who live in Jabodetabek and have minimal awareness of sustainable fashion products. The collected data were analyzed using WarpPLS 7.0 software, and a variance-based partial least squares-structural equation model (PLS-SEM) was applied to evaluate the hypothesized model.Findings/result: The findings show that consumers' perceived effectiveness has a positive significant influence on purchase intentions. Furthermore, consumers' perceived effectiveness positively influenced purchase intentions through attitudes.Conclusion: These findings show that this research model is partial mediation, where consumers' perceived effectiveness still has a positive significant effect on purchase intentions, with or without attitude as a mediating role.Originality/value (State of the art): Identifying attitudes in mediating the influence of Perceived consumer effectiveness on purchase intention. Keywords: sustainable fashion, perceived consumer effectiveness, purchase intention, attitude, fast fashion